THE EFFECT OF COMPENSATION TOWARDS EMPLOYEE PERFORMANCE AT CONCRETE INDUSTRY COMPANY IN RIAU INDONESIA - Srimulatsih, Mahbubah (Sekolah Tinggi Ilmu Ekonomi Riau, 2021)
The purpose of this research was to determine the effect of compensation towards employee performance at one of concrete company industry in Riau; PT. Semangat Hasrat Jaya Rimbo Panjang. The population in this study were all employees of PT. Hasrat Jaya spirit of 32 people. The data used are primary data and secondary data. This research used quantitative method and analyzed by simple linear regression. The result showed that the compensation has positive effect on employee performance. Based on Â the results of research analysis found tcount isÂ 7,633 while ttable is 2,042(7,633>2,042). Thus it can be concluded that the compensation variable (X) influences employee performance. Simple regression results showed Y = 34,902 + 0,173X. From the regression equation it is concluded that the regression coefficient of bX is positive. This shows that the independent variable if the equation is increased will cause an increase in the dependent variable. R Square results of 0.563 explain that employee performance is influenced by compensation of 56.3%.